The Green Story Book - Enid Blyton; Elleen A. Soper (Methuen & Co. Ltd. UK, 1947)
Mabel, W. Somerset Maugham The Barber's Uncle, William Saroyan The Rocking-Horse Winner, D.H. Lawrence Springtime on the Menu, O. Henry The Open Window, H.H. Munro (Saki) The Income-Tax Man, Mark Twain The Upper Berth, F. Marion Crawford My Bank Account, Stephen Leacock Silas the Good, H.E. Bates J. Thurber: The Catbird Seat
Keywords: General